2022
DOI: 10.3390/polym14153153
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposites Based on Polyamide 11/Diatoms with Different Sized Frustules

Abstract: Amorphous diatomite containing approx. 80% silicon dioxide SiO2 was used as a filler for a thermoplastic polymer of polyamide 11 obtained from natural sources. The diatomite particles of different sizes were previously fractionated by sedimentation to obtain powders with varying particle size distribution, including powders with or without frustule particles, crushed, uncrushed or agglomerated. Biocomposites containing 2.5, 5, 10 and 20% filler were tested for their mechanical properties, including tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…It was found that the addition of diatomite did not affect T g or T m to any significant extent. On the other hand, in the previous work [ 30 ], a more significant drop in T g was observed upon the addition of diatomite, showing that untreated diatomite presence causes formation of a filler–matrix interphase of weak interaction, with additional polymer freedom, while the filler treatment with APTES increases this interaction. The addition of diatomite caused a slight increase in the crystallisation temperature, showing some nucleation properties of the filler; however, silanization thereof caused no difference in this matter.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…It was found that the addition of diatomite did not affect T g or T m to any significant extent. On the other hand, in the previous work [ 30 ], a more significant drop in T g was observed upon the addition of diatomite, showing that untreated diatomite presence causes formation of a filler–matrix interphase of weak interaction, with additional polymer freedom, while the filler treatment with APTES increases this interaction. The addition of diatomite caused a slight increase in the crystallisation temperature, showing some nucleation properties of the filler; however, silanization thereof caused no difference in this matter.…”
Section: Resultsmentioning
confidence: 57%
“…The notch impact test was conducted for the composites both with the addition of silane and, comparatively, without silane, which was presented previously in [ 30 ]. Neat polyamide was characterised by the highest impact strength amongst the tested samples, 7 kJ/m 2 ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations